Fenomena Hidrolis Pada Pintu Sorong - Fahmiahsan, Rosyadah; Mudjiatko, Mudjiatko; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The sluice gate is a hydraulic structure that used for controlling the discharge on dam or irrigation canal. Their discharge coefficient depends on geometric and hydraulic parameters. Swamee (1992) presents two formulas for calculating the discharge coefficient (Cd) for free flow and submerged flow based on Henry’s Curve (1950). Laboratory models used to find out the flow phenomenon that was formed due to a difference in the edge shape of the sluice gate and increased gate base. The simulation done by varying the height of the gate opening (a) and the discharge (Q). The results of the study obtained the length of water jumps (Lj) formed on the sluice gate with edge 450 is longer than the sluice gate with edge 900. The discharge coefficient (Cd) value on the sluice gate with edge 450 is higher than the discharge coefficient (Cd) value on the gate with edge 900. The energy loss trendline (ΔE) obtained shows the value of ΔE increases with increasing h2/h1. The value of the critical flow coefficient range (Ckr) on the sluice gate with edge 450 and 900 increases with the increase in base height. The results of this study also add to the long trendline of previous research that has been done by Klaas (2009).Keywords: Discharge Coefficient, Energy Loss, Hydraulic Jump, Sluice Gate